The Role of Educational Games in Increasing Student Motivation and Engagement - Wahyuni, Erna; Tanuso, Nur Antoni Eko; Waruwu, Yaredi; Mata, Yessy; Putro, Adi Nugroho Susanto (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
Education is the learning of knowledge, skills, and habits of a group of people passed down from one generation to the next through teaching, research, and training, therefore an education must require a forum to achieve these goals. One example of a place to develop student education is a school, in a school there is a person who acts as a teacher or educator whose job is to develop the potential of students so that they can become an intelligent person. The purpose of this research is to find out a more in-depth discussion about the role of educational games in increasing student motivation and involvement in the learning process. This research was conducted to understand the role of the game given by an educator to students, whether the game in learning motivates students or not. The method used in this study uses a quantitative method that aims to examine the role of educational games through statistical techniques by collecting research variables using google form media and then imported and processed into the SPSS application and tested using the One Way Anova method. Based on the data obtained, it shows that the role of educational games in increasing student motivation and involvement is very influential, which is a good learning strategy that can have an effect in the teaching and learning process so that the role of the game can foster enthusiasm or motivation and student involvement in learning so that students become excited about learning and are not easily bored. The conclusion in this study explains that applying educational games as a learning medium is very important in the world of education, where the use of educational games in increasing student motivation and involvement can help increase student knowledge. So it can be concluded that games in education are very useful for students in the teaching and learning process to eliminate boredom and to motivate students in learning.